Variation in dry matter accumulation and growth indices of different mustard (Brassica juncea L.) hybrids as influenced by irrigation scheduling and sulphur fertilization - Kiran Rana,; JP Singh,; Rajesh Kumar Singh,; Manoj Parihar, (Journal of Oilseed Brassica, 2026)
A field experiment was carried out to assess the variation brought out by irrigation scheduling and sulphur fertilizationon the dry matter accumulation and growth indices of mustard hybrids during 2015-16 and 2016-17. The experimentwaslaid in split plot design withthree irrigation scheduling (0.4, 0.6 and 0.8 IW/CPE) and two hybrids (‘NRCHB-506’ and‘PAC 432’) as main plot treatment and three levels of sulphur (0, 30 and 60 kg S ha-1) as sub-plot treatment replicatedthrice. Results showed that application of irrigation at 0.8 IW/CPE, sulphur fertilization and cultivation of mustard hybrid‘PAC 432’ resulted in increment in dry matter accumulation at different growth stages as well as harvest. Further, thesetreatments were also adjudged superior in terms of growth indices viz., leaf area index (LAI), average growth rate (AGR),crop growth rate (CGR), leaf area duration (LAD) and biomass duration (BMD) in comparison to other treatments duringthe course of the trial. In relation to interactional effect of individual treatment variables, mustard hybrid ‘PAC 432’irrigated at 0.8 IW/CPE and fertilized with 60 kg S ha-1 produced maximum dry matter biomass while ‘NRCHB-506’irrigated at 0.4 IW/CPE and no sulphur application ensued least dry matter production.